Artificial Intelligence in Veterinary Pathology - Vishambhar Dayal Sharma; G. P. Jatav; Supriya Shukla; S. Pradeep; Anjali Sagar; Shivangi Upadhay; Manisha Chouhan; Surya Pratap Singh Parihar; Manoj Kumar Ahirwar (Techniques and Innovation in Engineering Research Vol. 4, 2022)
The simulation of human intelligence processes by machines, particularly computer systems, is known as artificial intelligence (AI). Learning, reasoning and self-correction are the three intelligence components that AI possesses. Strong AI systems can solve problems on their own when faced with new ones. The purpose of weak AI is to make robots act intelligently. Today, AI is being used in the healthcare industry to maintain digital health records and perform patient checkups with the aid of cutting-edge technologies. This chapter aims to discuss the utilization of Artificial Intelligence in Veterinary Pathology.